Changes in chlorine content over time – Probe deposit sampling in a Finnish kraft recovery boiler. (15th May 2023) - Balint, Roland; Engblom, Markus; Vainio, Emil; Laurén, Tor; Niemi, Jonne; Rautala, Jaakko; Saarinen, Timo; Hupa, Mikko; Hupa, Leena
Highlights: Increase in average deposit Cl content with time via diffusional vapour transport. Formation of Cl and K rich layer on steel surface due to deposit ageing. Sulfation of alkali chloride in deposits at low SO2 concentration in the gas phase. Increased deposit corrosiveness through local elemental enrichment and decreased T0. Abstract: Probe deposit samples of 1, 5, and 8 weeks exposure time were collected from the superheater area of a Finnish kraft recovery boiler. Deposit cross-sections were analysed regarding their morphology and chemical composition using SEM/EDXA. Morphological differences along the probe's circumference were observed due to different prevailing deposition mechanisms. Overall enrichment in the deposit Cl content with increasing exposure time was observed. The Cl enrichment proceeds via diffusion of Cl-vapours from the flue gas into the deposit. Two deposit ageing mechanisms were identified within the deposit samples. First, alkali chloride layers formed on the furnace-facing side of deposit particles and also directly on the steel surface as a result of deposit ageing. Second, within the 5 and 8-week probe samples, sulfation of alkali chloride within the inner regions of the deposits was observed. Analysis of the local first melting temperature of the deposits showed a significant decrease within the Cl and K-rich layer adjacent to the steel surface, implying an increased risk for melt formation, and thus corrosion, in the direct vicinity of the steel.